2016
DOI: 10.4103/2249-4863.184617
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence in the Solomon Islands

Abstract: The Solomon Islands has one of the highest rates of family and sexual violence (FSV) in the world with 64% of women aged 15–49 have reported physical and/or sexual abuse by a partner. The National Referral Hospital (NRH) in the capital, Honiara, is the only tertiary hospital for the country. Our 4-week medical elective at the NRH was spent reflecting on healthcare challenges including FSV, with the aim of identifying cases of FSV and assessing on the current strategies to improve care for victims. Throughout o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In our study, few women who experienced or witnessed gender-based violence reported the violence to an authority. This is consistent with other data that has found low rates of reporting of gender-based violence to formal authorities 17 28 30. There may be several reasons for this under-reporting including: social perceptions of violence against women, shame, financial barriers, fear of retribution, lack of awareness of services available for women who experience violence and lack of trust in healthcare workers, police or law enforcement 30–33.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, few women who experienced or witnessed gender-based violence reported the violence to an authority. This is consistent with other data that has found low rates of reporting of gender-based violence to formal authorities 17 28 30. There may be several reasons for this under-reporting including: social perceptions of violence against women, shame, financial barriers, fear of retribution, lack of awareness of services available for women who experience violence and lack of trust in healthcare workers, police or law enforcement 30–33.…”
Section: Discussionsupporting
confidence: 90%
“…The United Nations (UN) Human Development Index ranks the Solomon Islands as a low development country, with a rank of 152 out of 189 countries,16 with a history of political instability and conflict interrupting government services such as health and education 15. Unusual injury patterns which would raise concerns in Western hospitals are often not investigated in detail in the Solomon Islands, mostly due to limited resources, with healthcare workers having to accept the history provided 17. Often the cycle of abuse is carried onto subsequent generations; commonly perpetrators and victims have experienced childhood or adult trauma themselves 18 19…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ming et al 2016;Waka Mere 2019. Solomon Islands has high rates of family and sexual violence: 64 per cent of women aged 19 to 49 surveyed at the National Referral Hospital between 1994 and 2011 reported physical and sexual abuse from a partner.…”
mentioning
confidence: 99%